Museum, Memory and Cultural Heritage. Context of the Peruvian Independence, 1821-1826 - Cuadros Chávez, Hebner (2022)
The valuation of the historical memory of Peru through the cultural heritage and its relevance in the political ideology and in the discursive proposal, during the prelude and development of independence, determined the first proposals of cultural policies in the process of construction of the new Peruvian Republic. These conditions strengthened the political will of the authority, and the commitment to create the National Museum of Peru as an entity for safeguarding, education and recognition of historical-cultural memory. The present study offers an analysis and interpretation of the social factors that contributed to the value of the cultural legacy as a symbolic resource, in a historical period of Peru, and the effects on its development.